2020
DOI: 10.2478/orga-2020-0005
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Key Competency Model for Smart Factories in Production Processes

Abstract: Background and Purpose: The aim of the study is to develop a conceptual key competency model for smart factories in production processes, focused on the automotive industry, as innovation and continuous development in this industry are at the forefront and represent the key to its long-term success.Methodology: For the purpose of the research, we used a semi-structured interview as a method of data collection. Participants were segmented into three homogeneous groups, which are industry experts, university pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 44 publications
0
11
0
11
Order By: Relevance
“…One study reports that Industry 4.0 has the potential for job loss and human replacement by technological innovation (Ana et al, 2019). However, (Jerman, Bertoncelj, et al, 2020) emphasize that the discussion is not about job loss or gain, but about job restructuring and the ability of people to adapt to new digital technologies.…”
Section: Hr-digitalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reports that Industry 4.0 has the potential for job loss and human replacement by technological innovation (Ana et al, 2019). However, (Jerman, Bertoncelj, et al, 2020) emphasize that the discussion is not about job loss or gain, but about job restructuring and the ability of people to adapt to new digital technologies.…”
Section: Hr-digitalizationmentioning
confidence: 99%
“…University graduates represent a great potential in innovation, and thus play an important role in introducing Industry 4.0 (Vrchota et al, 2020). Therefore, it is necessary for educational organizations to be open to change (Jerman, Bertoncelj, et al, 2020; and to partner with the government (Matt et al, 2020) and industry to train a workforce with the required skills.…”
Section: Hr-managementmentioning
confidence: 99%
“…Numerous authors [26][27][28][29][30][31], [15] inventory the technical, digital, soft, innovative, management skills table for Industry 4.0. For example, in the paper [28] are inventoried 52 technical skills divided into State of the Art Knowledge Competencies and Skill; IT, Manufacturing, Computer Science and Robotics and Automation Competencies and Skills.…”
Section: Industry 40 Conceptsmentioning
confidence: 99%
“…Smart factories combine their solutions for sharing and monitoring, based on a comprehensive integration of manufacturing facilities and technologies. For this reason, Jerman et al (2020) identified the following key competencies needed by workers in smart factories (from the automotive industry): ICT and technical skills, innovation and creativity, openness to learning, adaptability, and various soft skills.…”
Section: Literature Reviewmentioning
confidence: 99%